Rancangan Program Sistem Komunikasi Alternatif Augmentatif Pada Anak Dengan Spektrum Autis - misda, Misdayani; Evilina S, Donna; Aprilia, Imas Diana (Jurnal Pendidikan Kebutuhan Khusus, 2023)
Assessment is the "spirit" in the world of special education. The results of the assessment are useful as a guide for serving children with special needs. Departing from the results of the assessment, a learning system or program can be designed and developed that suits the needs of the child. This study aims to find out about the results of the assessment of children with complex communication barriers (Complex Communication Needs) as a basis for making program designs in developing their communication. The research method used in this study is a qualitative research method by aligning theory with facts in the field so as to obtain in-depth information. The subjects in this study were children who experienced obstacles in communication and behavior interactions who also experienced complex communication barriers. The subject is currently studying at an SLB in the city of Bandung, precisely in Mekarjaya Kec. Rancasari. The result of this research is the formulation of an alternative and augmentative communication program design called MacDi. MaCDi can be used by other subjects with the same traits and characteristics as the subjects in this study.